Science Web-Module Integrated with Tannery Waste as Local Potential to Improve Students’ Problem Solving - Atznain Iqma Miswami; Heru Nurcahyo (Biosaintifika: Journal of Biology & Biology Education, 2020)
Problem solving skills are very important skill students must owned. The low score of students’ problem solving skills becomes a serious problem in the 21st century teaching and learning. The development of science web-based module integrated with tannery waste as local potential became a research that must be done. This research examined the appropriateness and the effectiveness of a science web-based module integrated with tannery waste as local potential in improving students’ problem solving skills. The Four-D research and development model was employed, consisting of define, design, develop, and disseminate. This research was conducted in the form of pretest posttest control group design. The appropriateness analysis conducted by content expert, teaching media expert, and science teacher indicating that the product was categorized very good. The effectiveness of the learning was tested using the independent sample t test with sig. value set at 0.000. The test showed that the science teaching done using the science web-based module was effective in improving students’ problem solving skills in SMP Negeri 1 Wungu. The product resulted from this study is expected to overcome the teaching and learning problems associated with the low score of students' problem-solving skills. Moreover, it can provide a real experience and independence to students in using the science web-based module to study.